Applications of solid wastes based heterogeneous catalyst: a review - Chi, Cheng Chong; Setiabudi, H. D. (Universiti Malaysia Pahang, 2018)
Solid wastes arose as an apprehension nowadays because of their handling and disposal issues. The major solid wastes are eggshell, fly ash, oil palm based wastes and rice husk ash, which are discarded over million tonnes around the world. Rather than to be served as no economic value waste, these residues consist of high silica content, which prompted its other applications, such as its adoption as an economical and environmental-friendly catalyst. In the present work, an attempt to provide an overview of the applications of solid wastes as heterogeneous catalysts in various processes was done. According to the literature reviewed, the vast feasibility of the solid wastes as heterogeneous catalysts was proven, in which tremendous variation of highly valuable products could be obtained via the assistance of the synthesized cheap and green catalysts. The reported literature provided a benchmark for further widen the possible applications of these solid waste based heterogeneous catalysts.